Pengaruh Metode Pembelajaran Kooperatif Terhadap Kemampuan Sosial Siswa di Sekolah Dasar Negeri 1 Kota Serang - Suganda, Ahmad (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to determine the effect of cooperative learning methods on students' social skills at State Elementary School 1 Serang City. Social skills are one of the important aspects in students' development, especially in building positive interactions with peers and teachers. Cooperative learning methods are expected to improve students' social skills through group work, effective communication, and respect for differences. This study used a quantitative approach with an experimental design. The research sample consisted of two groups, namely the experimental group using cooperative learning method and the control group using conventional learning method. Data were collected through observations, interviews, and questionnaires measuring aspects of students' social skills before and after the application of learning methods. The results showed that there was a significant increase in the social skills of students using cooperative learning methods compared to the control group. This indicates that cooperative learning can be an effective strategy to improve students' social skills at State Elementary School 1 Serang City. This study provides recommendations for cooperative learning methods to be applied more widely in elementary schools to support the development of students' social skills to the fullest.